2018
DOI: 10.1136/bmj.k1046
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, non-communicable disease risk factors, and walking speed in older adults: multi-cohort population based study

Abstract: ObjectiveTo assess the association of low socioeconomic status and risk factors for non-communicable diseases (diabetes, high alcohol intake, high blood pressure, obesity, physical inactivity, smoking) with loss of physical functioning at older ages.DesignMulti-cohort population based study.Setting37 cohort studies from 24 countries in Europe, the United States, Latin America, Africa, and Asia, 1990-2017.Participants109 107 men and women aged 45-90 years.Main outcome measurePhysical functioning assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 44 publications
5
76
0
4
Order By: Relevance
“…Whereas cross‐sectional and longitudinal survey studies have found that most mental disorders are associated with poor educational attainment , a recent register‐based study from the Netherlands founded that schizophrenia, but not depression or bipolar disorder, were associated with lower likelihood of obtaining secondary or higher education . Taken together, it seems that mental disorders can lead to irregular work careers and permanently low income, thus increasing the total economic burden of mental disorders .…”
Section: Introductionmentioning
confidence: 97%
“…Whereas cross‐sectional and longitudinal survey studies have found that most mental disorders are associated with poor educational attainment , a recent register‐based study from the Netherlands founded that schizophrenia, but not depression or bipolar disorder, were associated with lower likelihood of obtaining secondary or higher education . Taken together, it seems that mental disorders can lead to irregular work careers and permanently low income, thus increasing the total economic burden of mental disorders .…”
Section: Introductionmentioning
confidence: 97%
“…Aging has been defined as the “time‐dependent decline of functional capacity and stress resistance, associated with increased risk of morbidity and mortality” (Burkle et al, 2015). Environmental stressors, including lifestyle and social adversity (Stringhini et al, 2018), psychological disorders (Chiu et al, 2018; Wolf & Morrison, 2017), and genetic factors (McDaid et al, 2017) may influence the aging process, leading to differing aging rates. Traditionally, quantitative assessment of “the rate of aging” relies on the analysis of mortality curves of populations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there seems to be no previous studies on personality and disability‐free life years. The concept of disability‐free life years extends the measurement of life expectancy by considering the years people can live without having any disabling conditions or morbidity that limits their ability to carry out daily activities (Stringhini et al, ). A long life is valuable, but a healthy and fully functional long life is even more valuable.…”
Section: Introductionmentioning
confidence: 99%